“Mombrain and Sticky DNA”: The Impacts of Neurobiological and Epigenetic Framings of Motherhood on Women's Subjectivities - Norrmén-Smith, Ingrid Olivia; Gómez-Carrillo, Ana; Choudhury, Suparna (Frontiers in Sociology, 2021)
The fields of epigenetics and neuroscience have come to occupy a significant place in individual and public life in biomedicalized societies. Social scientists have argued that the primacy and popularization of the “neuro” has begun to shape how patients and other lay people experience themselves and their lifeworlds in increasingly neurological and genetic terms. Pregnant women and new mothers have become an important new target for cutting edge neuroscientific and epigenetic research, with the Internet constituting a highly active space for engagement with knowledge translations. In this paper we analyze women’s reception to the translations of nascent epigenetic and neuroscientific bodies of research. We combine two methodological approaches: (i) a circumscribed digital ethnography and (ii) focus groups with pregnant women and new mothers. Here we focus on the qualitative results from our focus groups. Our findings record how engagement with translations of epigenetic and neuroscientific research impact women’s perinatal experience, wellbeing, and self-construal. Three themes emerged in our analysis: 1) A kind of brain; 2) Looping effects: the authority of the biomedical narrative and its relationship with the perinatal experience; 3) Imprints of past experience and the management of the future. The data drawn from our participants reveal how mothers engage with the neurobiological style of thought increasingly characteristic of public health and popular science messaging around pregnancy and motherhood: through the molecularization of pregnancy and child development, a typical passage of life becomes saturated with 'susceptibility', 'risk' and the imperative to preemptively make 'healthy' choices, in turn redefining and shaping the experience of what it is to be a 'good', 'healthy' or 'responsible' mother/to-be.